Head and neck size and neck strength predict linear and rotational acceleration during purposeful soccer heading - Caccese, J. B.; Buckley, T. A.; Tierney, R. T.; Arbogast, K. B.; Rose, W. C.; Glutting, J. J.; Kaminski, T. W. (Sports Biomechanics, 2018)
There is increasing societal concern about the long-term effects of repeated impacts from soccer heading, but there is little information about ways to reduce head impact severity. The purpose of this study was to identify factors that contribute to head acceleration during soccer heading. One-hundred soccer players completed 12 controlled soccer headers. Peak linear (PLA) and rotational (PRA) accelerations were measured using a triaxial accelerometer and gyroscope. Head acceleration contributing factors were grouped into 3 categories: size (head mass, neck girth), strength (sternocleidomastoid, upper trapezius) and technique [kinematics (trunk, head-to-trunk range-of-motion), sternocleidomastoid and upper trapezius activity]. Multiple regression analyses indicated size variables explained 22.1% of the variance in PLA and 23.3% of the variance in PRA; strength variables explained 13.3% of the variance in PLA and 17.2% of the variance in PRA; technique variables did not significantly predict PLA or PRA. These findings suggest that head and neck size and neck strength predict PLA and PRA. Anthropometric and neck strength measurements should be considered when determining an athlete`s readiness to begin soccer heading.